Crystallizing Transmembrane Peptides in Lipidic Mesophases - CAFFREY, MARTIN (My University, 2010)
Structure determination of membrane proteins by crystallographic means has been facilitated by crystallization in lipidic mesophases. It has been suggested, however, that this so-called in meso method, as originally implemented, would not apply to small protein targets having ?4 transmembrane crossings. In our study, the hypothesis that the inherent flexibility of the mesophase would enable crystallogenesis of small proteins was tested using a transmembrane pentadecapeptide, linear gramicidin, which produced structure-grade crystals. This result suggests that the in meso method should be considered as a viable means for high-resolution structure determination of integral membrane peptides, many of which are predicted to be coded for in the human genome.
PUBLISHED
Keywords: Biochemistry; Peptides; membrane proteins